Sissies online: Taiwanese male queers performing sissinesses in cyberspaces 1. - Lin, DennisC. (Inter-Asia Cultural Studies, 2006)
The Internet has led to the creation of a variety of virtual worlds, which inspire and empower local male queers, through their virtual reality, relative safety and increased accessibility, to perform their sissy selves, which, though at different levels, might need to be suppressed in real life. The virtual ‘sissinesses’ performed by local male queers may be perceived as multiple ongoing processes of interactions as well as a variety of contested sites of power relations, through and within which the queers interact with other users and Internet technologies. Moreover, their virtual sissinesses become involved with the socio‐cultural, psychic and material conditions that incessantly intersect with one another. All these conditions and interactions thereby come to confront the reflexive agencies of the queers in order to negotiate diverse, ever‐changing sissy identities and representations in cyberspaces. More significantly, their virtual sissinesses are characterised by resisting the regimes of heterosexism, gender dimorphism, biological determinism, heterosexual masculine supremacy and compulsory gay masculinity. It is through these resisting implications that they have commenced an era of online sissy queer politics.